Kualitas Fisik dan Organoleptik Telur Asin dari Berbagai Jenis Telur Unggas - Ahmad Bayu Ariawan; Harapin Hafid (JURNAL GALUNG TROPIKA, 2021)
Salted egg is an egg preservation product that aims to improve the taste, aroma, appearance of the yolk, and color through salt diffusion into the egg. This study aims to compare various types of eggs on the physical and organoleptic qualities of salted eggs. This study used a completely randomized design (CRD) consisting of 4 treatments, namely duck eggs (P0), broiler eggs (P1), free-range chicken eggs (P2), and duck eggs (P3). Parameters measured in this study were egg yolk and white pH, egg weight loss, and organoleptic quality. The results showed that using various types of eggs had a significant effect (p<0.05) on egg yolk pH, weight loss, yolk color, egg yolk texture, saltiness, saltiness level, and acceptance of salted eggs. However, it had no significant effect (p>0.05) on egg white pH, egg white color, salted egg aroma, white egg texture, and salted egg taste. Goat eggs are the best type in optimal pH and are the most preferred by consumers organoleptically.